Centrum usług społecznych szansą na wzmocnienie procesu deinstytucjonalizacji - Zbyrad, Teresa Jadwiga (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2023)
The article discusses the importance of the process of the deinstitutionalisation of adult social care, as implemented by social service centers (CUS). This innovative form aims at integrating social services in the community, without forcing many elderly and disabled people to abandon their places of residence. Surveys show that nursing homes are publicly viewed as a last resort rather than a desired option. Residing in an institution will never equal living in one’s own home. A nursing home is an institution in the full sense of the word, and will never replace a family home. New regulations in Poland empower local authorities to create communal social service centers. This innovative form of service implementation allows for the provision of services covering people’s living environments, without a necessity for a person to move into a nursing home. In addition, the nursing homes will get a chance to reduce the number of dwellers, which may help them reorganize and enhance the quality of services provided.